Factors Associated with Genital Hygiene Behaviors in Cervical Cancer Patients in Surakarta, Indonesia - Umami, Afriza; Sudalhar, Sudalhar; Lufianti, Anita; Paulik, Edit; Molnár, Regina (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: Maintaining genital cleanliness is essential for women since intimate organ problems can cause female tract infections. Poor genital hygiene can affect sexually transmitted infections, and therefore, it is prominent to investigate factors related to genital hygiene behaviors in women to reduce this type of infection.Purpose: This study aimed to find out the factors associated with genital hygiene behaviors in cervical cancer patients.Methods: A case-control study was conducted on cervical cancer patients in Surakarta, Indonesia, from December 2017 to February 2018. A structured questionnaire was used to collect data from 178 subjects using a fixed disease sampling technique that consisted of 56 cases of poor genital hygiene behaviors and 122 controls of good genital hygiene behaviors with a comparison of 1:2. The dependent variable was genital hygiene behaviors, while the independent variables were stress, exposure to social media regarding genital hygiene, environmental sanitation, husband’s education, and support. Logistic regression was employed for data analysis.Results: Genital hygiene behaviors increased with exposure to social media related to genital hygiene (OR=9.20; 95% CI=3.87 to 21.87, p<0.001), good environmental sanitation (OR=5.16; 95% CI=2.19 to 12.14, p<0.001), high husband’s education (OR=6.49; 95% CI=2.23 to 18.91, p=0.001) and support (OR=2.88; 95% CI=1.24 to 6.67, p=0.013). Women who experienced psychological problems such as stress showed decreased genital hygiene behaviors (OR=0.25; 95% CI=0.94 to 0.71, p=0.009).Conclusions: Genital hygiene behaviors in women increased with exposure to social media related to genital hygiene, adequate environmental sanitation, high husbands’ education, and support. In contrast, stress decreased women’s behaviors in practicing genital hygiene. These findings emphasize the need for women to improve genital hygiene behaviors as well as for nurses to explain how to increase women's genital hygiene behaviors.